Linguo-Creativity in the Communicative Space of Fantasy Genre (Proceedings of Southern Federal University. Philology, 2019)
Elena V. Murugova, Alena O. Pustovetova (Rostov-on-Don, Russian Federation)The complex structural-semantic and functional analysis is performed by the linguocreative activity of J.R.R. Martin in the communicative space of the fantasy genre. The research material is the toponyms selected from the saga of J.R.R. Martin “The Song of Ice and Fire”, the cycle of works “The Knight of the Seven Kingdoms”, the cartographic collection “The Land of Ice and Fire”, and the accompanying book “The World of Ice and Fire”. Within the framework of considering the problem of constructing a secondary world of works of the fantasy genre, the authors classify toponyms by type of object, analyze the ways of forming fictional toponyms, and consider the author’s occasional narratives in detail as a special labeling of territories according to the principle of one-on-one opposition.Key words: linguocreative activity, fantasy, toponyms, secondary world, occasionalisms, word-formation models.DOI 10.23683/1995-0640-2019-3-96-104